Characterization of particle-laden jet flows in inertia-dominated regime. (December 2022) - Haghshenas, Armin; Groll, Rodion
Abstract: Point-particle large eddy simulations are used to characterize a vertical particle-laden round jet in inertia-dominated regime. Both particle–fluid and particle–particle interactions are considered, and a stochastic approach is adopted to model wall roughness. We fix the Reynolds number in the turbulent regime and vary the Stokes number based on the pipe bulk parameters over two orders of magnitude between 10 and 1000. We find that the decay and spreading rates of particle concentration grow with Stokes number and wall roughness. The particle concentration field, however, reaches a self-similarity in the jet far field, where the radial profiles follow a Gaussian-like function. We identify a regime change in the particle velocity field, which is characterized by a local Stokes number ( S t l ) defined based on the centerline particle velocity and its half-width. For S t l ≳ 20, referred to as unresponsive regime, particles accelerate within the near field but retain their momentum within the far field, where the radial particle velocity profiles follow a self-similar basic exponential function. For S t l ≲ 10, referred to as responsive regime, particles retain their momentum within the near field but decelerate within the far field, where the radial profiles follow a self-similar Gaussian-like function. Transition from unresponsive to responsive regime occurs within the far field when S t l reduces from 20 towards 10. Highlights: Simulation of particle flow in pipe is necessary to obtain a reliable particle jet flow. Decay and spreading rates of particles grow with Stokes number and wall roughness. Wall-roughness effects are intensified as Stokes number is increased. A local Stokes number characterizes the regime change in particle velocity field.